Late Holocene shorelines in east Attica (Greece). - Evelpidou, N.; Karkani, A.; Kampolis, I.; Pirazzoli, P. (Quaternary International, 2017)
A coastal and submarine geomorphological investigation took place in the coasts of eastern Attica, aiming to identify palaeoshorelines. Former sea-level positions were deduced from emerged and submerged tidal notches. Eight fossil shorelines were deduced in the study area; two emerged ones at about +24 ± 30 and +40 ± 30 cm, and six submerged ones at about −22 ± 30 (modern), −40 ± 30, −60 ± 30, −80 ± 30, −130 ± 30 and −460 ± 30 cm. It is worth mentioning that a rather different tectonic behavior may be distinguished between the south (AT1-AT5) and the north (AT10-AT28) part of the study area.